Mortality and Incidence of Hospital Admissions for Stroke among Brazilians Aged 15 to 49 Years between 2008 and 2012 - Adami, Fernando; Santos Figueiredo, Francisco Winter dos; Paiva, Laercio da Silva; Sa, Thiago Herick de; Sousa Santos, Edige Felipe de; Martins, Bruno Luis; Valenti, Vitor Engracia [UNESP]; Abreu, Luiz Carlos de (Public Library Science, 2016)
Introduction The objective was to analyze rates of stroke-related mortality and incidence of hospital admissions in Brazilians aged 15 to 49 years according to region and age group between 2008 and 2012. Methods Secondary analysis was performed in 2014 using data from the Hospital and Mortality Information Systems and the Brazilian Institute of Geography and Statistics. Stroke was defined by ICD, 10th revision (I60-I64). Crude and standardized mortality (WHO reference) and incidence of hospital admissions per 100,000 inhabitants, stratified by region and age group, were estimated. Absolute and relative frequencies; and linear regression were also used. The software used was Stata 11.0. Results There were 35,005 deaths and 131,344 hospital admissions for stroke in Brazilians aged 15-49 years old between 2008 and 2012. Mortality decreased from 7.54 (95% CI 7.53; 7.54) in 2008 to 6.32 (95% CI 6.31; 6.32) in 2012 (beta = -0.27, p = 0.013, r(2) = 0.90). During the same time, incidence of hospital admissions stabilized: 24.67 (95% CI 24.66; 24.67) in 2008 and 25.11 (95% CI 25.10; 25.11) in 2012 (beta = 0.09, p = 0.692, r(2) = 0.05). There was a reduction in mortality in all Brazilian regions and in the age group between 30 and 49 years. Incidence of hospitalizations decreased in the South, but no significant decrease was observed in any age group. Conclusion We observed a decrease in stroke-related mortality, particularly in individuals over 30 years old, and stability of the incidence of hospitalizations; and also regional variation in stroke-related hospital admission incidence and mortality among Brazilian young adults.